Novel Making of Bacterial Cellulose Blended Polymeric Fiber Bandages - GÜNDÜZ, OĞUZHAN (WILEY-V C H VERLAG GMBH, 2018)
Bacterial cellulose (BC) is a very promising biological material. However, at present its utilization is limited by difficulties in shape forming it. In this Communication, it is shown how this can be overcome by blending it with poly(methylmethacrylate) (PMMA) polymer. BC:PMMA fibers are produced by pressurized gyration of blended BC:PMMA solutions. Subsequently, BC:PMMA bandage-like scaffolds are generated with different blends. The products are investigated to determine their morphological and chemical features. Cell culture and proliferation tests are performed to obtain information on biocompatibility of the scaffolds.
Keywords: bacterial cellulose; bandages; polymer; pressurized gyration; TISSUE ENGINEERING APPLICATIONS; WOUND DRESSING APPLICATIONS; PRESSURIZED GYRATION; NANOFIBERS; PROLIFERATION; MEMBRANES; ADHESIVE; SCAFFOLD; SKIN